A comparison study of the impact of ZnO nanoparticles and ZnSO4 in wastewater treatment processes - Huang, Xi Tong (2015)
The impacts and fate of ZnO nanoparticles and ZnSO4 in wastewater treatment processes were investigated through the stability study of ZnO nanoparticles in wastewater at different pH and a continuous period of exposure to ZnO nanoparticles. The ZnO nanoparticles and ZnSO4 were introduced to eight bioreactors with 1 Liter capacity with dosage of 1mg/L, 10mg/L, 20mg/L and 50mg/L for ZnO and Zn2+ as ZnSO4 for 300 minutes. The stability of ZnO nanoparticles showed the highest dissolution at low pH, and showed decreasing dissolution with pH. The results of COD (chemical oxygen demand) removal efficiencies demonstrated that heavier dosage of both ZnO and ZnSO4 inhibited the removal of COD, and ZnSO4 had a larger impact on inhibition of COD removal in wastewater at high dosage with a lower efficiency of COD removal compared to ZnO nanoparticles. Although the Zinc (ZnO and ZnSO4) concentration found in the sludge was relatively low for both, the removal efficiency of Zinc from wastewater was in the range of 80% to more than 90% which suggested that removal of nanoparticle through biosorption might still be valid to some extent while a large part of Zinc might likely to be deposited on the wall of bioreactor as observed in this research study. Through the bacterial viability assessment and FESEM (Field Emission Scanning Electron Microscope) analysis, the live-to-dead cell ratio indicated that wastewater bacterial cells might be resilient to ZnO nanoparticles and ZnSO4 but they were able to cause the change of shape and size of activated sludge, as can be seen in the images from FESEM. The results presented in this study may be able to yield insight that the impact of ZnO nanoparticles and ZnSO4 on wastewater treatment was significant in terms of removal efficiency as reflected in various indicators such as COD removal and overall removal rate.